Effect of selectivity at simultaneous impact on inertial sensor of kinematic and acoustic load - Карачун, Володимир Володимирович; Мельник, Вікторія Миколаївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article reveals the nature of the additional zero shift of a gyroscope at flight. Attention is focused on the appearance of the systematic component of the zero shift at asynchronous rolling of a fuselage, due to the effect of selectivity of frequencies of acoustic vibration of the surface of suspension of gyroscope by the angular motion of the device. It turns out that asynchronous, as well as synchronous fuselage rolling can cause the systematic zero shift. However, it takes place only at the simultaneous action with the acoustic emission. The transition of the surface of the suspension of sensors from the solid state into impedance causes the appearance of Euler inertial forces that cause the zero shift of devices and, as a result, causes additional measurement errors during their usage. The results can be used for testing works and for the creation of new hypersonic devices. One should consider the possibility of an additional zero shift of the initial sensor at flight, as well as implement the means to form the acoustic comfort of the on-board equipment